Role managerial accountant applying for target costing in institution private sectors which higher competition in market KSA: Analytical study - Mousa, Ezzat Kamal Abdalla; Akola, Osama Abdelmonge (Journal of Economic, Administrative and Legal Sciences, 2025)
The research aimed to clarify the basic role of the management accountant in making decisions related to the target cost. The research problem was the lack of participation of management accountants in an effective manner during the design of products or the pricing of services in a professional manner. The lack of experience for those working in markets with strong competition in the application of the target cost. The importance of research is reflected in clarifying the role of the management accountant in the field of determining the target cost. Determining the cost of the product on scientific, sound and practical grounds The establishment lies in implementing its plans in an effective manner and achieving good competitive advantage in light of the analysis of the internal and external data and information of the entity, which can be determined in the realization of its objectives. The study relied on a number of approaches, including inductive, inductive, historical and analytical descriptive using the random sample method. Management accountants must participate effectively during product design.